REPRESENTASI LOVE LANGUAGE DALAM VIDEO MUSIK CINCIN KARYA HINDIA - Naja Kayra Rahim; Yusanto, Freddy (Ilmu Komunikasi, FISIP Universitas Pasundan, 2024)
Love is an inherent aspect of human life. Its presence is important and can be attained through a romantic relationship. To create a healthy, quality relationship, harmonious communication is necessary with your partner. This is where the concept of love languages comes in, as a way to express love both verbally and non-verbally for your loved ones. Love languages then became a very interesting topic of discussion among the public, and were applied in everyday life through various communication media, one of which was music videos, especially the music video Cincin by Hindia. This is a qualitative research that employs Roland Barthes semiotic analysis approach, and the data was obtained through direct observation. The purpose of this research was to comprehend how the signs of Love Languages are depicted in the music video Ring by Hindia. In this music video, the concept of love languages is represented through the lyrics and each scene. Starting from words of affirmation, physical touch, quality time, receiving gifts, and serving, which represent the concept of love languages, are shown in every scene of this music video.